CORRECTION OF PSYCHOLOGICAL SET AS A RESPONSE TO STRESS - Sakvarelidze, R.; Bzhalava, T. (Modern Psychology, 2020)
The study is based on the following assumption: Any integrated state of the subject (psychological set) involves a program for system modification and is formed as a response to the perception of this or that object /event. Replacement of the stress program with the placidity and self-confidence program is theoretically and practically important. Examination of emotions, training related experience and the theory of set imply that to correct set as a response to stressful experience it is advisable to use not only relaxation, but also the predisposition toward fight and self-confidence as well as focusing one’s attention on the relevant parts of the body, particularly the spine.
Keywords: stress, relaxation, self-confidence, psychological set.